Exploring EFL Students’ Perception on Self and Peer Assessment in Academic Writing - Dhea Agustianingsih; Wahyudin Wahyudin; Andi Patmasari; Darmawan Darmawan (MASI Mandiri Edukasi, 2026)
In English as a Foreign Language (EFL) contexts, academic writing remains a challenging skill for students, particularly in evaluating writing quality and monitoring learning progress. To address this issue, self-assessment and peer-assessment have been implemented as formative assessment strategies in writing instruction. This study aimed to investigate students’ perceptions of self- and peer-assessment in academic writing courses. A descriptive quantitative research design was employed. Data were collected through a closed-ended questionnaire consisting of 18 Likert-scale items, administered to 100 third-semester students of the English Education Study Program at Tadulako University. The data were analysed using descriptive statistics, including frequencies and percentages. The findings revealed that most students held positive perceptions of self- and peer-assessment. These strategies were perceived as helpful in identifying strengths and weaknesses, enhancing awareness of the writing process, and improving writing quality. However, a few students expressed neutral perceptions, indicating a need for clearer guidelines and a more structured implementation. Overall, the results suggest that self-assessment and peer-assessment are effective approaches for developing EFL students’ academic writing skills.